ANALYSIS OF USING EFFICIENT LOGGING TOOLS AT PT. PURWA PERMAI IN CENTRAL KALIMANTAN - Suhartana, Sona; Yuniawati, Yuniawati (Secretariat of Forestry Research and Development Agency, 2008)
A high log demand that often exceeds its supply capability should be overcome by using appropriate logging Â tools. Numerous Â kinds and types of logging Â tools require Â a well planning in their utilization. Number of tools which are greater or fewer than what is actually needed can be disadvantageous Â for a company. In relevant to these aspects, a study was carried out at a timber estate in Central Kalimantan Â in 2007. The aim of the study was to find out an efficient number Â of tools used for logging Â in a timber Â estate. The analysis was based on the target and realization of the companyâs log production. The result revealed that: (1) Optimum number of logging tools depended on production target, Â i.e. 41 units Â of chainsaws Â for felling, Â 42 units Â of farm tractors Â for skidding, Â 9 units of loaders for loading and unloading, and 36 units of trucks for transportation; (2) Number Â of logging tools as obtained from all activities Â in the field was fewer than that from Â the analysis based on production target and realization. This condition Â indicated that number of logging tools used in the company was not yet efficient.